LEARNING SITUATIONS IN PANDEMIC CONTEXTS. ARE THEY NEW ONES? - Nathalia Valeria Mezzano; Erica Eliana Ojeda; Mariana Leonor Aguirre (Universidad Nacional del Nordeste, 2021)
The article analyzes and reflects on new learning situations arising from the context of Preventive and Compulsory Social Isolation in 2020 due to the pandemic caused by SARSCoV-2 virus, and as stated by Decree No. 297/20. The article focuses on the core idea of Virtual learning in boys' and girls' education and teacher training: debates and proposals. With this aim, the research recovers practicum experiences carried out for the Chair "Integration, Research and Practice Workshop IV", of the Early Education Teaching Training Programme at Faculty of Humanities, National University of the Northeast, from November to December 2020. In this paper, the experiences of two students beginning their teaching practicum, are analyzed. The analysis is also carried out with interviews to the head of the kindergarten, where the training was performed, and to the family of a girl student. seeking to link theoretical concepts that explain the relationship between learning, bonding, corporeality in this new context.